The carbon footprints of alternative value chains for biomass energy for cooking in Kenya and Tanzania. (August 2017) - Okoko, Abigael; Reinhard, Juergen; von Dach, Susanne Wymann; Zah, Rainer; Kiteme, Boniface; Owuor, Samuel; Ehrensperger, Albrecht
Abstract: Due to its availability and affordability for poorer populations, wood-based biomass energy remains vital in meeting local energy demands – especially for cooking fuel – in many regions of the developing world. However, increasing feedstock scarcity (e.g. due to deforestation) coupled with the negative socio-economic and environmental outcomes of inefficient production and consumption technologies make it imperative to identify alternative energy solutions that benefit people without harming the environment. Indeed, tackling energy poverty is crucial to efforts aimed at meeting sustainable development goals at the household level. However, interventions aimed at reducing energy poverty must simultaneously seek solutions that might reduce people's carbon footprint. Carbon footprints, or the amounts of greenhouse gas emissions linked to particular activities, are associated with climate change and its impacts. Globally, calls have intensified to reduce the carbon footprint of energy use, including use of biomass fuels. Locally, climate change issues are increasingly seen as posing particular threats to already vulnerable communities. The present paper evaluates the carbon footprints of alternative biomass energy solutions for cooking, as one key aspect of their environmental performance. It compares the carbon footprints of firewood, charcoal, biogas, jatropha oil, and crop residue briquettes. The research focuses on selected technologies for biomass energy production and consumption in two case study sites in rural and urban contexts of Kenya and Tanzania. Carbon footprinting is applied as a methodological approach to evaluating technological options for sustainable development in developing economies undergoing rapid population growth, urbanization, and industrial development. Results indicate that the unimproved charcoal value chain has a big carbon footprint. The value chain for jatropha oil appears to hold the greatest potential for carbon footprint reductions, as long as the feedstock is grown in the form of hedges around plots. However, the limited yield potential of hedges calls into question the economic viability of this solution. Results further show that carbon footprinting can help to raise awareness and inform stakeholders and decision-makers about alternative, environmentally more suitable biomass energy value chains. However, any assessment of the overall sustainability of these value chains should also integrate socio-economic aspects and factors influencing adoption.